A card game to renew urban parks: Face-to-face and online approach for the inclusive involvement of local community. (April 2020) - Menconi, M.E.; Tasso, S.; Santinelli, M.; Grohmann, D.
Highlights: An inclusive method for a participatory renewing of urban parks is developed. The participatory method dedicated to a park takes account of the entire urban green network. For inclusive participation, we integrate face-to-face and online approaches. We develop a civic medium dedicated to parks' participatory renovation. We develop an innovative structured listening method focusing on urban green network evaluation. Abstract: Urban parks are often designed and renewed using standardized models that fail to incorporate the different functions and services required by the local communities served. Furthermore, when the citizens are involved in co-design, the participation processes are seldom fully inclusive, and the results are not representative of the entire local community. The paper starts from these considerations for developing an innovative participatory design method to renew urban parks. This method simultaneously uses multiple and alternative participation tools for adapting to the different technical skills of the citizens and to their inclinations. Furthermore, it entails the analysis and interpretation of the expectations of the local community in light of the urban green network. The method uses the conceptual framework of the SWOT analysis and the Trochim's concept mapping for developing a card game playable face to face or online. The results of the card game are processed using the statistical analysis to identify the main design themes (the clusters), and to split the participants' suggestions into different design alternatives. Successively, the participants vote these alternatives for selecting the renewal design respondent to the local community's needs.